FRPRCS-5 fibre-reinforced plastics for reinforced concrete structures proceedings of the fifth International Conference on Fibre-Reinforced Plastics for Reinforced Concrete Structures Cambridge, UK, 16-18 July 2001. Volume 2 - Burgoyne, C. J. (Thomas Telford, 2001)
Fibre reinforced plastics are increasingly being used as replacements for steel reinforcement in concrete structures. The reinforcement can be untensioned, or it can be in the form of prestressing tendons. This is the 2nd volume of the proceedings from a conference on the subject.
Keywords: Reinforced concrete construction -- Congresses.; Fibre reinforced plastics -- Congresses.; elektronické knihy; electronic books